THE ROLE OF ECONOMICS IN EXPLAINING THEFT BEHAVIOR: A LITERATURE REVIEW - Agustian, Luthfi Nur; Wiyono, Vincent Hadi (Journal of Applied Economics in Developing Countries, 2021)
This article aimed at reviewing discussions on the role of economics in explaining criminal behavior, particularly theft. From pioneering work of Becker in 1968 up to the 2013 empirical work of Maddah in Iran this review comes to a number of following proposition. First, economics has contributed significantly at understanding many theft determining factors and also policy options derived from those studies. Second, to fully understand the criminal behavior, economics alone is good but not enough. A holistic approach is required because the acts are motivated by many drives, rationally as well as irrationally which can only understood triangularly. Finally, theft redistributes income, does not increase welfare, just waste resources from thief, household and society. Keywords: Economics; Theft; Social Cost